INTERFERON TREATMENT OF INFANTS WITH INTRAUTERINE INFECTIONS - O. V. Shamsheva; I. V. Polesko (Детские инфекции (Москва))
The article describes the results of clinical diagnostic methods for risk assessment childbirth with intrauterine infection, data from clinical trials with a high level of evidence efficacy VIFERON® in adjuvant therapy in preterm infants with severe intrauterine viral infections.